2006
DOI: 10.1038/sj.bmt.1705392
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged responses after autologous stem cell transplantation in African-American patients with multiple myeloma

Abstract: Multiple myeloma (MM) has a double incidence in African-American (AA) than in non-AA patients and previous studies have shown a higher mortality in the former patient population. Here, we retrospectively analyzed the results of autologous stem cell transplantation (ASCT) in 38 AA and 32 non-AA consecutive patients. The two groups were comparable at diagnosis for age, stage of the disease, cytogenetic abnormalities, b 2 microglobulin and albumin blood levels, and plasma cell marrow infiltration. The rates of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A few studies have compared survival patterns between African-American and Caucasian patients treated with both conventional therapy and autologous stem cell transplantation and have reported similar outcomes. [48][49][50] As it cannot be ruled out that there are differences with regard to access to care, referral bias and other types of biases, there is need for larger studies assessing MM outcomes by race. Ideally such studies should include molecular analyses.…”
Section: Other Clinical and Biological Racial Disparity Patternsmentioning
confidence: 99%
“…A few studies have compared survival patterns between African-American and Caucasian patients treated with both conventional therapy and autologous stem cell transplantation and have reported similar outcomes. [48][49][50] As it cannot be ruled out that there are differences with regard to access to care, referral bias and other types of biases, there is need for larger studies assessing MM outcomes by race. Ideally such studies should include molecular analyses.…”
Section: Other Clinical and Biological Racial Disparity Patternsmentioning
confidence: 99%
“…We favor the latter hypothesis based on results observed in our center where both AA and non-AA patients have equal access to care. In our previous study, 4 the overall response rate after induction treatment and disease-free survival after ASCT in AA patients was 51% and 21 months, respectively, whereas in this current study, they are 92% and 28 months, respectively, consistent with improvements conferred by the newer myeloma agents followed by allo-SCT. Our results, although in a limited number of patients, suggest that IMIDs and/or bortezomib obtain good and comparable responses in AA and non-AA MM patients, and these responses are further improved with auto-SCT in both patient groups.…”
mentioning
confidence: 42%
“…2,3 Although comparable outcomes of AA and non-AA patients with standard chemotherapy were previously demonstrated, it is not known whether IMIDs or bortezomib can improve the outcome in MM patients of different ethnicity. 4 To address this question, we consecutively analyzed 56 newly diagnosed MM patients (26 AA, 30 non-AA) who received induction therapy at our institution from January 2003 to June 2011. All of the patients received induction therapy with one or more of the new agents (IMIDs or bortezomib) in addition to either dexamethasone or prednisone (Table 1).…”
mentioning
confidence: 99%
“…Contrary to earlier reports, AA patients in our analysis had shorter PFS (15.6 months) than the 21 and 60.5 months reported earlier in two smaller series. 9,10 This difference may be related to the smaller cohort of patients in these analyses. Furthermore, whereas most of the patients in our series were local residents of southeast Michigan with easy access to the transplant centers, the distance traveled to the transplant centers was not addressed in the report by Verma et al This might have impacted the frequency of follow-up and resulted in early diagnosis of asymptomatic biochemical relapse as opposed to a late symptomatic relapse.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, there is no study addressing the influence of pre and post transplant prognostic variables of known importance for CA on the outcomes in AA. Saraf et al 9 reported a superior median event-free survival of 21 months in 38 AA patients compared with 12 months in 32 non-AA patients after auto-SCT for MM; (P ¼ 0.02). 9 In a similar analysis, Verma et al 10 reported a prolonged median PFS and OS of 60.5 and 95.2 months, respectively, in 36 AA patients with MM after auto-SCT compared with a PFS and OS of 43.7 and 68.5 months, respectively, in 55 CA controls, but the differences were not statistically significant (P ¼ 0.46 and 0.41, respectively).…”
Section: Introductionmentioning
confidence: 99%